A pilot survey on knowledge, attitude and practice towards the Islamisation of knowledge as perceived by the staff of Kulliyyah of Allied Health Sciences, International Islamic University Malaysia - Shahdan, Intan Azura; Rahmat, Sarah; Zahari, Ilyanoon; Syed Abdul Rahman, Sharifah Nurul Natasha; Mohd Shafri, Mohd Affendi (Kulliyyah of Medicine, International Islamic University Malaysia, 2018)
This preliminary study investigated the: (i) level of knowledge, attitude and practice (KAP) among members of Kulliyyah of Allied Health Sciences (KAHS), International Islamic University Malaysia (IIUM) regarding Islamisation of knowledge (IOK); (ii) correlation of KAP and IOK with the duration of service and level of exposure to IOK-related activities; (iii) comparison of KAP between departments in KAHS towards the understanding of IOK, and (iv) level of KAP in IOK between KAHS academics and non-academic staff. Since studies on the integration of religious worldview in health sciences faculties are scarce, this study will be investigating the effectiveness of IOK programmes at the faculty level. A total of 74 staff participated in the study. The response rate was 65.5% out of 113 distributed questionnaires. All respondents have average knowledge (50±28%) in IOK and showed positive attitude (78±32.5%) towards IOK. The knowledge of Islamisation in KAHS correlates positively with the duration of service (p<0.05) and the level of exposure to IOK-related activities (p<0.05). However, answers given to some questions indicated that the staff perceptions and knowledge of IOK are ambiguous and may suggest a misunderstanding of the Islamisation term. Furthermore, an average score was found among the academic respondents with regards to their integration of IOK into practice. These shortcomings may affect the integration and implementation of IOK either in classrooms, clinics or offices and lead to a poor integration of the Islamisation agenda to the students as well as the patients. Hence, there is a need to design workshops and programmes more towards practical approaches of IOK into health-based sciences as well as the implementation of IOK agenda at the workplace, rather than the theoretical aspects per se. In conclusion, most of the respondents have positive attitude towards the IOK movement in KAHS despite the high level of knowledge among some members, in particular the academic staff, is not yet translated into practice.